Evaluación de las variables del desempeño cooperativo con enfoque en el buen vivir de las provincias de Napo y Pastaza - Cedeño Valdez, Blanca Patricia (2017)
This research was carried out with the purpose of evaluating the cooperative performance aimed at the achievement of Good Living in the savings and credit cooperatives of the Napo and Pastaza provinces, establishing the application of phases such as: to identify the existing variables through the collection of bibliographical information as social balances of Cooperativism, Popular and Solidarity Economy, Good Living and Corporate Social Responsibility; in the following phase the interview was developed to the managers of these cooperative associations in order to know the number of partners and employees with whom they count; in addition, we selected the suitable experts who helped in the process taking into account the work experience and professional profile; then the survey model was elaborated, consisting of 9 cooperative principles with the respective variables that were applied to 11 managers or presidents of the credit unions, 85 employees and 378 members, the latter being the result of the formula applied to the population object of study. The data obtained from the surveys were shown through the application of radar graphs determined by principles and analyzed, which reflected that these associations must improve their performance in relation to compliance with the principles of Good Living, and as the last phase was elaborated a plan with fourteen improvement actions that will help eradicate the weaknesses detected in the cause and effect diagram or Ishikawa.